The Effect of Job Stress on Public Service Motivation and Job Performance on Employees at Bintang Semarapura Hospital General Hospital - Putu Shine Amanda Megayana (Institute of Computer Science (IOCS), 2021)
This research was conducted to determine job stress effect on employee’s public service motivation and job performance. The sample in this study were employees at RSU Bintang Semarapura Bali as many as 134 respondents. Data was collected by distributing questionnaires containing 20 questions with a Likert scale of 1-5 based on the simple random sampling method. Data analysis using PLS-based SEM method. The results of this study state that challenge stress has a positive and significant direct effect on job performance and public service motivation. However, hindrance stress has a direct and significant negative effect on job performance and public service motivation. Meanwhile, public service motivation has been shown to mediate the positive effect between challenge stress on job performance and negatively between hindrance stress on job performance.